Serum Uric Acid and Cardiovascular or All-Cause Mortality in Peritoneal Dialysis Patients: A Systematic Review and Meta-Analysis - Liu, Zhi-qiang; Huang, Zhi-wen; Kang, Shu-ling; Hu, Chan-chan; Chen, Fa; He, Fei; Lin, Zheng; Yang, Feng; Hu, Zhi-jian (Frontiers in Cardiovascular Medicine, 2021)
Background: Studies have shown inconsistent associations between serum uric acid (SUA) levels and mortality in peritoneal dialysis (PD) patients. We conducted this meta-analysis to determine whether SUA levels were associated with cardiovascular or all-cause mortality in PD patients. Methods: PubMed, Embase, Web of Science, the Cochrane Library, CNKI, VIP, Wanfang Database, and trial registry databases were systematically searched up to April 11, 2021. Cohort studies of SUA levels and cardiovascular or all-cause mortality in PD patients were obtained. Random effect models were used to calculate the pooled adjusted hazard ratio (HR) and corresponding 95% confidence interval (CI). Sensitivity analyses were conducted to assess the robustness of the pooled results. Subgroup analyses and meta-regression analyses were performed to explore the sources of heterogeneity. Funnel plots, Begg's tests, and Egger's tests were conducted to evaluate potential publication bias. The GRADE approach was used to rate the certainty of evidence. This study was registered with PROSPERO, CRD42021268739. Results: Seven studies covering 18,113 PD patients were included. Compared with the middle SUA levels, high SUA levels increased the risk of all-cause mortality (HR=1.74, 95%CI: 1.26-2.40, I2=34.8%, τ2=0.03), low SUA levels were not statistically significant with the risk of all-cause or cardiovascular mortality (HR=1.04, 95%CI: 0.84-1.29, I2=43.8%, τ2=0.03; HR=0.89, 95%CI: 0.65-1.23, I2=36.3%, τ2=0.04; respectively). Compared with the low SUA levels, high SUA levels were not statistically associated with an increased risk of all-cause or cardiovascular mortality (HR=1.19, 95%CI: 0.59-2.40, I2=88.2%, τ2=0.44; HR=1.22, 95%CI: 0.39-3.85, I2=89.3%, τ2=0.92; respectively). Conclusion: Compared with middle SUA levels, high SUA levels are associated with an increased risk of all-cause mortality in PD patients. SUA levels may not be associated with cardiovascular mortality. More high-level studies, especially randomized controlled trials, are needed to determine the association between SUA levels and cardiovascular or all-cause mortality in PD patients.